A Study of Clinico-Pathological Characteristics of Endometrial Carcinoma with Respect to Grading - Chhabra, Raval; Patel, Prem S; Tiwari, Aishani; Dayal, Anupama; Panchal, Divyesh N (Annals of Pathology and Laboratory Medicine, 2024)
Background: Endometrial cancer is an emerging health concern in India, largely affecting postmenopausal women due to lifestyle changes and demographic factors. This study aims to analyze the clinicopathological characteristics of EC in Indian patients to improve diagnosis, prevention, and treatment. Materials and Methods: This retrospective study included 50 patients who underwent radical hysterectomy for EC at a tertiary care center over six years. Data was collected on demographic and tumor characteristics and clinical outcomes, including age, parity, menopausal status, tumor type, FIGO grade, stage, size, myometrial invasion, lymphovascular invasion, and lymph node metastasis. Statistical analysis determined the significance of these factors in prognosis and survival. Results: The mean age at diagnosis was 62 years, with 86% of patients being postmenopausal. The most common type was endometrioid carcinoma (82%). Significant prognostic factors included tumor size, myometrial invasion, lymphovascular invasion, lymph node status, and FIGO staging. High-grade tumors exhibited a higher incidence of lymphovascular invasion (80% vs. 42.5%, p-value = 0.033) and poorer survival outcomes (50% vs. 81.3% alive, p = 0.049). FIGO staging, lymph node metastasis, and lymphovascular invasion were statistically significantly correlated with mortality. Conclusion: EC primarily affects postmenopausal women, with endometrioid carcinoma being the most common type. Prognostic factors such as tumor size, myometrial invasion, lymphovascular invasion, and lymph node status influence treatment decisions and patient outcomes. High-grade tumors are associated with more aggressive disease and worse survival rates, highlighting the importance of thorough nodal evaluation and tailored treatment approaches. This study enhances the understanding of EC, aiding in the development of improved diagnostic and management strategies.